2017
DOI: 10.1111/1750-3841.13759
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Metabolic Pathways and Absorption of Sea Cucumber Saponins, Holothurin A and Echinoside A, in Vitro and in Vivo

Abstract: Sea cucumber saponins (SCSs) exhibit a wide spectrum of bioactivities, but their metabolic characteristics are not well elucidated. In this study, the metabolism of holothurin A (HA) and echinoside A (EA), 2 major saponins in sea cucumber, by gut microflora were investigated. First, we conducted an in vitro study, where in the SCSs were incubated with intestinal microflora and the metabolites were detected by high pressure liquid chromatography-high resolution mass spectrometry. We also conducted an in vivo st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Meanwhile, all three deglycosylated metabolites of HA were detected in the serum, and the peak contents were 0.4, 0.2, and 0.3 μg/mL, respectively, which was only 0.67–1.33% of HA. Only one of the three metabolites of EA (E1) was detected with a peak of 0.04 μg/mL in the serum of rats, while the peak of EA in the serum was 1.8 μg/mL . It could be proved that the deglycosylated metabolites of EA and HA could have existed in the serum after oral administration of the SCSs.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Meanwhile, all three deglycosylated metabolites of HA were detected in the serum, and the peak contents were 0.4, 0.2, and 0.3 μg/mL, respectively, which was only 0.67–1.33% of HA. Only one of the three metabolites of EA (E1) was detected with a peak of 0.04 μg/mL in the serum of rats, while the peak of EA in the serum was 1.8 μg/mL . It could be proved that the deglycosylated metabolites of EA and HA could have existed in the serum after oral administration of the SCSs.…”
Section: Resultsmentioning
confidence: 97%
“…The LC–MS/MS system was used to determine HA, EA, and metabolites in the serum, liver, and small intestinal contents . Chromatographic separations were achieved on an Agilent 1260 HPLC separation system (Palo Alto, CA, USA) using a Proshell 120 EC-C18 (3.0 mm × 150 mm, 2.7 μm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…715 Metabolism of triterpenoids holothurin A and echinoside A, both by incubation with gut microora (in vitro) or in vivo in rats, identied deglycosylation to be the dominant process. 716 The proles of triterpenoid glycosides in ve different body components (respiratory trees, body walls, gonad tubules, guts, and aquapharyngeal bulbs) of the sea cucumber Eupentacta fraudatrix were found to be qualitatively similar but with some variability in minor compounds. 717 Transcriptome sequence data for three brittle star species (Ophionotus victoriae, Amphiura liformis, Ophiopsila aranea) identied a number of neuropeptide precursor proteins.…”
Section: Echinodermsmentioning
confidence: 98%
“…The active chemical of ECH is phenylethanoside, which displays antioxidant, anti-fatigue, anti-tumor and anti-inflammatory effects, and can improve memory, nerve and liver protection, and enhance immune regulation. 16,17 In the study on db/db diabetic mice, it was found that ECH could improve insulin resistance, increase HDL level, and reduce TG, TC and LDL levels, indicating that ECH could effectively improve diabetic lipid metabolism. 18 In addition, Shimoda et al proved that echinoside could affect lipid metabolism by regulating mRNA related to hepatobiliary sterol transport and metabolism.…”
Section: Introductionmentioning
confidence: 99%